2001
DOI: 10.1007/s11745-001-0723-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in conjugated linolenic acid composition within samples obtained from a single source

Abstract: Conjugated linoleic acid (CLA; 9c,11t-18:2) and CLA isomers have been reported, in animals, to exhibit a variety of health-related benefits. Silver ion high-performance liquid chromatography (Ag-HPLC) was found to provide better resolution of the isomers than gas chromatography. Most commercially available samples of CLA, prepared by base-catalyzed isomerization of linoleic acid (9c,12c-18:2), are composed of mixtures of four major isomers. While these isomers have been characterized, we found significant chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The profiles of CLA isomers in oils produced during hydrogenation differed greatly with differing hydrogenation times (Table 1). The identity of the biologically active CLA isomers is not clearly known, although it is generally assumed to be the cis-9,trans-11 isomer (peak 1) for anticarcinogenic properties and the trans-10,cis-12 isomer (peak 4) for fat partitioning activity (6,24,25). Recently, however, it has been reported that other types of CLA isomers also have a biological activity (26).…”
Section: Resultsmentioning
confidence: 99%
“…The profiles of CLA isomers in oils produced during hydrogenation differed greatly with differing hydrogenation times (Table 1). The identity of the biologically active CLA isomers is not clearly known, although it is generally assumed to be the cis-9,trans-11 isomer (peak 1) for anticarcinogenic properties and the trans-10,cis-12 isomer (peak 4) for fat partitioning activity (6,24,25). Recently, however, it has been reported that other types of CLA isomers also have a biological activity (26).…”
Section: Resultsmentioning
confidence: 99%
“…cis -9, trans -11-CLA ( c 9, t 11-CLA) is the primary isomer naturally present in dairy and ruminant meat products that contributes to about 80% of the total dietary CLA intake in the human diet ( , ). In contrast, synthetic CLA preparations generally consist of two major CLA isomers, trans -10, cis -12-CLA ( t 10, c 12-CLA) and c 9, t 11-CLA, and they are the major CLA isomers in supplemental products ( ). CLAs have been reported to exhibit a wide range of promising beneficial effects in both in vitro cell culture and in vivo animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has recently been shown that the quality of the commercially available CLA products is highly variable, in that the actual content of the various CLA isomers in the tablets varies substantially among the different preparations studied (73,74). Finally, commercial CLA products (often CLA mixtures with high content of the c10,t12 isomer, together with other isomers) are usually considered dietary supplements.…”
Section: Discussionmentioning
confidence: 99%